World wide scheme launched by UK Dairy Association - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The United Kingdom Dairy Association (UKDA) has launched a new initiative to tell the world's dairy industry what services it has to offer. UKDA, representing scientific, technological, educational, and commercial organizations in the OK dairy...